Deformation of surrounding rock in a shallow large-section tunnel passing through soft-plastic loess layer - Yang, Yuan; Liu, Liu; Liu, Yang; Zhang, Haotian; Guo, Congnan (Frontiers in Earth Science, 2025)
In view of the problem of the plastic state of the surrounding rock of loess high-speed railway tunnels changing from hard plastic to soft-plastic, even in a flow-plastic state with increasing moisture content, and appearing collapse and large deformation of support structure, it is put forward to use advanced pipe-roof support. Numerical simulation and site monitoring and measurement are adopted to analyze the tunnel surrounding rock deformation characteristics when different soft-plastic layer thicknesses (1 m, 3 m, 5 m) distributing on tunnel arc, sidewall and invert, and the control effect of advanced pipe-roof support to tunnel construction deformation. Results show: ① The spatial distribution of soft-plastic loess layer has a much greater impact on deformation than its thickness. Vertical and horizontal displacements of the tunnel surrounding rock appear three stages: rapid deformation during the initial stage of excavation, continuous slow deformation and tending towards stable convergence deformation. ② Compared to the situation of no pipe–roof, implement of advance pipe-roof support can significantly improve the control effect of vertical and horizontal displacements of the tunnel surrounding rock. ③ The tunnel surrounding rock deformation characteristics show: it is crucial to control the deformation of surrounding rock from the initial excavation stage to the primary support and sealing before forming a ring. The use of advanced pipe-roof support has a significant effect on controlling deformation during the construction of soft-plastic loess high-speed railway tunnels.